AN ANALYSIS OF CRITICAL THINKING SKILLS IN READING BETWEEN GENDERS - Raturomon, Lidya Theresye (Journal of Language, Education, Literature, and Culture, 2024)
The research aims to find out and explain if English Study Program students of AWCU show any difference found between genders in critical thinking skills in reading. Five critical thinking skills, namely Interpretation, Explanation, Analysis, Inference, and  Evaluation, were tested among 57 male and female respondents. The descriptive data analysis showed that the overall mean score for each critical thinking skill in reading was generally not manifested; the score was below 50 after being judged using the California Critical Thinking Skills (CCTS) scale, meaning that some efforts were needed to improve it. Oneway Anova for data analysis was used, and it was found that, from the five critical thinking skills investigated, the explanation skill showed different significance between male and female students. Its alpha value was 0,003 between males and females on this skill. The other four skills did not show any significant difference between genders, with Interpretation skill being 0.711, Analysis 0.489, Evaluation 0.920, and Inference being 0.459.